Bifurcation Analysis in a Kind of Fourth-Order Delay Differential Equation - Xiaoqian Cui; Junjie Wei (Discrete Dynamics in Nature and Society)
A kind of fourth-order delay differential equation is considered. Firstly, the linear stability is investigated by analyzing the associated characteristic equation. It is found that there are stability switches for time delay and Hopf bifurcations when time delay cross through some critical values. Then the direction and stability of the Hopf bifurcation are determined, using the normal form method and the center manifold theorem. Finally, some numerical simulations are carried out to illustrate the analytic results.